Faktor-Faktor yang Berhubungan dengan Perilaku Penanganan Dismenore Primer pada Siswi SMA Negeri 1 Dondo - Suci Anggraeni; Medyza Nanda (LPPM Universitas Harapan Bangsa, 2023)
Dysmenorrhea is a gynecological disorder that is often found in young women. Dysmenorrhea that often occurs is primary dysmenorrhea. The incidence of dysmenorrhea in the world averages more than 50% in women in each country (WHO, 2015). Meanwhile in Indonesia it reaches 55% in productive age. The purpose of this study was to find out what factors were related to handling behavior Primary dysmenorrhea in students of SMA Negeri 1 Dondo. This research method is analytic with a cross sectional approach. The research was conducted at SMA Negeri 1 Dondo with a population of 156 students and a sample of 61 students using simple random sampling technique. Data were collected by questionnaire, univariate and bivariate analysis using Chi-square with the help of SPSS. The research results obtained from 61 respondents, respondents in the late age category 50.8% and middle age 49.2%, respondents with less knowledge 62.3% and sufficient knowledge 82.6%, respondents with good family support 78.7%, and less 21.3%, respondents with positive handling behavior 62.3%, and negative as much as 37.7%. After doing bivariate analysisusing chi-squareobtained factors that have a relationship with primary dysmenorrhea treatment behavior is Knowledge (p = 0.011) and Family Support (p = 0.046) while those that do not have a relationship is Age (p = 0.429). The conclusion of this study is that there is a significant relationship with the behavior of handling primary dysmenorrhea in students of SMA Negeri 1 Dondo is Knowledge and Family Support while there is no significant relationship is age